Factors Influencing the Body Composition of Adolescents and Young Adults with Down Syndrome - Bathgate, Katherine Elizabeth (Curtin University, 2018)
The aim of this thesis was to describe the body composition of adolescents and young adults with Down syndrome and relationships with physiological, behavioural and social factors including dietary intake and physical activity. A high proportion of adolescents and young adults with Down syndrome had an anthropometry and body composition indicative of overweight and obesity. Young people with Down syndrome need to be supported to be more physically active and consume a healthier diet.